Kecerdasan Spiritual dan Kecerdasan Emosional terhadap Organizational Citizenship Behavior (OCB) pada Aparatur Sipil Negara - Malahayati, Malahayati; AS, Asmaran; Komalasari, Shanty (Jurnal Al-Husna, 2020)
Organizational Citizenship Behavior (OCB) is the behavior of the extra outside the description the work in the organization or agency carried out by the individual. OCB is the voluntary behaviors that are not listed in the description of the work and not known directly in the formal award system but it gives a positive impact for agency. OCB is able to give a sense of comfort in the environment agency as well as contribute indirectly toward the effectiveness of agency. Therefore, the researcher wants to conduct the research about the influence of spiritual intelligence and emotional intelligence to Organizational Citizenship Behavior (OCB) at state civil apparatus at the Ministry of Religion Banjarmasin. In this study, researcher used quantitative-field research method. Population in this research 69 state civil apparatus at the Ministry of Religion Banjarmasin. Based on research that was conducted at the Ministry of Religion Banjarmasin. The results of this study showed: 1) There are significant influence between the influence of spiritual intelligence and emotional artifice to Organizational Citizenship Behavior (OCB) at state civil apparatus at the Ministry of Religion Banjarmasin with significant level 0,006 (p < 0,05) and giving the effective impact 17,1%. 2) There are significant influence between the influence of spiritual intelligence and emotional artifice to Organizational Citizenship Behavior (OCB) at state civil apparatus at the Ministry of Religion Banjarmasin with significant level,005 (p < 0,05) and giving the effective impact 13,1%. 3) There are significant influence between the influence of spiritual intelligence and emotional artifice to Organizational Citizenship Behavior (OCB) at state civil apparatus at the Ministry of Religion Banjarmasin with significant level 0,011 (p < 0,05)  and giving the effective impact 11,1%.